Study on the Wear-resisting Performance of Automobile Engine Timing Sleeve Chain - Xu Xiuqin; Zhao Jianxiang; Meng Fanzhong (Jixie chuandong)
The wear test of 05 CT automobile engine timing chain of slit sleeve and seamless sleeve is carried out,the results show that,under the same experimental conditions,the pin and sleeves of two different forms all have cyclic softening phenomenon more or less after the chain went through high-speed wear test,and the softening degree of slit sleeve is less than that of the seamless sleeve. Under the condition of oil jet lubrication,the lubrication and cooling condition of slit sleeve chain is better than that of seamless sleeve chain,and the wear resistance of slit sleeve is better than that of seamless sleeve.